2021
DOI: 10.5187/jast.2021.e107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of applying cellulase and starch on the fermentation characteristics and microbial communities of Napier grass (Pennisetum purpureum Schum.) silage

Abstract: Competing interestsNo potential conflict of interest relevant to this article was reported. Funding sourcesState funding sources (grants, funding sources, equipment, and supplies). Include name and number of grant if available.This study was supported by a research project on the public welfare industry (Agriculture) from the Ministry of Agriculture of China (Grant number. 201503134).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
2
11
0
Order By: Relevance
“…Escherichia coli appeared in ensilage at 3 and 7 days and disappeared at 14, 30, and 60 days, possibly due to the decrease in lactic acid content during the ensilage process [ 30 ], which led to a decrease in environmental pH and inhibited the growth of Escherichia coli . Filamentous fungi gradually decreased with the extension of ensilage time and disappeared after 30 days of ensilage, but they were present in the CK_60 and C_30 treatment groups, which may be caused by the change in environmental components and acidity during the ensilage process [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli appeared in ensilage at 3 and 7 days and disappeared at 14, 30, and 60 days, possibly due to the decrease in lactic acid content during the ensilage process [ 30 ], which led to a decrease in environmental pH and inhibited the growth of Escherichia coli . Filamentous fungi gradually decreased with the extension of ensilage time and disappeared after 30 days of ensilage, but they were present in the CK_60 and C_30 treatment groups, which may be caused by the change in environmental components and acidity during the ensilage process [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in WSC content after 60 d in silage can be explained by the hydrolysis of starch, being consistent with the decrease in starch in silage at the same period. Previous studies showed an increase of 3-4% WSC by adding starch to the silage [48,49]. The increase in WSC after conservation indicates the potential for starch hydrolysis to contribute to carbohydrate availability, suggesting avenues for enhancing silage quality through supplementation strategies.…”
Section: Fermentative Characteristics Of African Stargrass Silage And...mentioning
confidence: 92%
“…There are various types of enzymes used as feed supplements in the livestock industry, which can be largely divided into a single enzyme (SE) and a multienzyme complex (MC) [ 14 , 15 ]. An example of a SE (β-mannanase) is a type of enzyme that targets hard-to-digest ingredients in feed, and an enzyme complex is intended to simultaneously increase the digestibility of various nutrients in feed by adding diverse enzymes at the same time [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%